The association between varus knee deformity and morphological changes in the foot and ankle in patients with end-stage varus knee osteoarthritis - Zhenchao Huang; Zian Zhang; Wenzhe Wang; Fan Chen; Haining Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Background This study aimed to (1) determine the association between varus knee deformity and ipsilateral foot and ankle morphology, and (2) evaluate the relationship between varus knee deformity and foot and ankle pain in patients with end-stage varus knee osteoarthritis (KOA). Methods A total of 213 patients who underwent primary total knee arthroplasty for end-stage varus KOA were enrolled in this study and divided into a ‘severe varus group’ (n = 119) and a ‘mild varus group’ (n = 94) based on preoperative knee varus degree. Morphological parameters and pain incidence in the foot and ankle were compared between the two groups. The correlation between knee varus and foot and ankle morphology was analyzed. Results Significant differences in ankle morphology were observed between the two groups. The deformity magnitudes of the hindfoot valgus (P < 0.001) and hallux valgus (HVA, P = 0.028; IMA, P = 0.046) were significantly higher in the severe varus group. Additionally, the incidences of ankle osteoarthritis (OA) (P = 0.005) and hallux valgus (P = 0.028) were higher in the severe varus group. Patients with severe KOA were more likely to experience medial ankle pain (P = 0.023), hindfoot pain (P = 0.034), and multiple pain locations (P = 0.015). Conclusion Varus knee deformity was associated with morphological changes in the foot and ankle, and the incidence of ankle OA and hallux valgus deformity was significantly higher in patients with severe varus KOA. Patients with severe varus KOA were more prone to medial ankle pain, hindfoot pain, and multiple pain locations, which were associated with corresponding morphological changes.